2016
DOI: 10.1186/s12885-016-2712-4
|View full text |Cite
|
Sign up to set email alerts
|

Dactolisib (NVP-BEZ235) toxicity in murine brain tumour models

Abstract: BackgroundGlioblastomas (GBMs) are highly malignant brain tumours with a poor prognosis, and current cytotoxic regimens provide only a limited survival benefit. The PI3K/Akt/mTOR pathway has been an attractive target for therapy due to its high activation in GBMs as well as other cancers. The dual pan-PI3K/mTOR kinase inhibitor dactolisib (NVP-BEZ235) is an anti-neoplastic compound currently under investigation. However, little is known about its efficacy in human GBMs. We aimed at evaluating the efficacy of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 41 publications
3
11
0
Order By: Relevance
“…2b ). This is consistent with the results by Netland and coworkers who found no survival benefit or inhibition of tumour growth in orthotopic xenograft models of GB developed in nude rats and NOD/SCID mice [ 19 ]. Accordingly, the simultaneous treatment with NVP-BEZ235 and the MAPK inhibitor AZD6244 did not lead to synergistic radiosensitization of tumor cells, questioning a radiosensitizing effect of both inhibitors [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…2b ). This is consistent with the results by Netland and coworkers who found no survival benefit or inhibition of tumour growth in orthotopic xenograft models of GB developed in nude rats and NOD/SCID mice [ 19 ]. Accordingly, the simultaneous treatment with NVP-BEZ235 and the MAPK inhibitor AZD6244 did not lead to synergistic radiosensitization of tumor cells, questioning a radiosensitizing effect of both inhibitors [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…was chosen due to significant toxicity of higher doses towards our animals (data not shown). Consistently, in two independent animal studies utilizing nude rats and NOD/SCID mice in orthotopic xenograft models of GB, Netland and coworkers have found severe side effects of doses of NVP-BEZ235 higher than 25 mg/ml [ 19 ]. The early termination of recent NVP-BEZ235 clinical trials due to elevated toxicity may confirm that safety dosing of NVP-BEZ235 should be thoroughly investigated prior to use [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 76%
“…Employment of new drugs and therapeutic strategies may cause additional side effects. Our data showed weight loss around 7% in animals treated with BEZ235, while other studies have reported weight loss greater than 15% [56]. Studies have shown that the loss of body weight, after oral administration of BEZ235, occurs in a dose-dependent manner in several model systems [14,57,58].…”
Section: Discussionsupporting
confidence: 45%
“…Recent studies have highlighted conflicting results regarding the effectiveness of this agent in vivo where BEZ235 demonstrated antitumor efficacy with improved survival against U87MG orthotopic gliomas in one study [ 67 ]. However, very little to no efficacy was observed in another independent orthotopic xenograft model study [ 68 ]. It is important to note that many PI3K/mTOR inhibitors demonstrate weak affinities for ABC transporters, but in spite of this, can still achieve target inhibition in GBM albeit with modest single-agent efficacy.…”
Section: Hif Transcription Factorsmentioning
confidence: 99%